Enhancing Student Learning Interest through Product-Based Learning and Peer Assessment in Sustainable Bakery Practicum Using Watermelon Rind and NTT Palm Sugar - Yunus Karyanto; Rina Asmaul; Diana Evawati; Kama Ratih Sholikha (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the implementation of Product-Based Learning (ProdBL) integrated with peer assessment in a bakery practicum and its contribution to student learning interest. The study employed a pre-experimental design with a one-group pretest-posttest approach involving 20 third-semester students of the Culinary Education Study Program. Data were collected using a validated learning interest questionnaire and supported by classroom observations and student reflections. The results of the paired sample t-test showed a significant difference between pretest and posttest scores (t = -2.816, p = 0.011 < 0.05), indicating an increase in student learning interest. The mean score improved from 31.15 in the pretest to 37.65 in the posttest. Qualitative findings revealed that students became more active, confident, and collaborative during the practicum process. The use of watermelon rind as food waste and local palm sugar contributed to meaningful and contextual learning experiences. These findings suggest that the integration of ProdBL and peer assessment can enhance student learning interest and support sustainability-oriented vocational education.